Development and validation of a scale to measure hypertensive Chinese individual's behavior toward salt reduction consumption - Le Han; Ying Liu; Xiao Liu; Peng Xian (BMC, 2024)
Abstract Objective This study aimed to develop and validate the Salt Reduction Behavior Scale (SRBS) to measure the behavior of hypertensive Chinese individuals in adhering to salt reduction practices. Methods The SRBS was constructed based on the Health Belief Model, consisting of five constructs: knowledge, perceived severity, perceived benefits, perceived barriers, and cues to action. Data were collected from 2,082 hypertensive patients in Beijing, China, who completed a questionnaire administered through an online platform. Kaiser-Meyer-Olkin (KMO) test was used to assess the adequacy of the sample and the Bartlett's test of sphericity to examine the factorability of the dataset. Confirmatory Factor Analysis (CFA) was used to assess the structural validity and reliability of the SRBS. Results The KMO analysis yielded a notably elevated value of 0.95, indicating that the data was highly suitable for Exploratory Factor Analysis (EFA). Bartlett's test of sphericity yielded a statistically significant test statistic (P < 0.001). The 32-item SRB questionnaire demonstrated strong internal consistency with a Cronbach's alpha coefficient of 0.923. A second-order Confirmatory Factor Analysis (CFA) revealed that, after removing the unrelated construct of barriers, SRB could be represented by four sub-constructs: knowledge, severity, benefits, and action. The final version of the SRBS consists of 21 items. These items displayed high factor loadings, indicating a strong relationship between the items and their respective sub-constructs. The discriminant validity analysis revealed that the SRBS sub-constructs were distinct from each other. The SRBS scores were positively correlated with self-reported salt reduction practices. This demonstrates that individuals with higher SRBS scores were more likely to engage in actual salt reduction behaviors, indicating concurrent validity. Conclusion The results illustrate that the Salt Reduction Behavior Scale is a robust and comprehensive instrument for assessing salt reduction behavior among hypertensive Chinese individuals. The scale's specific sub-constructs provide a detailed understanding of their knowledge, attitudes, and practices related to salt consumption. Healthcare professionals and policymakers can utilize this tool to tailor interventions and educational programs to encourage healthier dietary habits, thereby reducing the risk of cardiovascular diseases in China.